German citizens' preference for domestic carbon dioxide removal by afforestation is incompatible with national removal potential - Christine Merk; Ulf Liebe; Jürgen Meyerhoff; Katrin Rehdanz (Communications Earth & Environment, 2023)
Efficient and sustainable solutions for offsetting residual emissions via carbon dioxide removal are a major challenge. Proposed removal methods result in trade-offs with other Sustainable Development Goals, and the removal needs of many countries exceed their domestic potentials. Here, we examine the public acceptability of conducting afforestation and direct air capture programmes domestically in Germany or abroad. To uncover the relative importance of various programme attributes, we use a multifactorial vignette experiment. We find that afforestation receives stronger support than direct capture. Next to the costs to households, minimising environmental impacts on biodiversity in forests and the use of renewable energy for direct capture are more important for acceptability than the permanence of storage. Further, individuals strongly prefer domestic programmes to offsets in other countries. These findings suggest significant discrepancies between strong public preferences for domestic carbon removal with low environmental side-effects and the too low potential for such removals.
Keywords: 330